PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA GHATHAF COFFEE PREMIUM TEUPIN PUNTI ACEH UTARA - Rahmi; Sutoyo; Ferdiananda Chadafi, Muhammad; Rahmati, Rahmati; Husna, Syifa Ul (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2024)
This study aims to identify the influence of product quality and service quality on customer satisfaction at Ghathaf Coffee Premium, Teupin Punti, North Aceh. The research method used is quantitative with a survey approach. Data were collected through questionnaires distributed to 75 regular customers who have experience with Ghathaf Coffee Premium products and services, and the data were processed using SPSS 29. The results of regression analysis show that product quality has a positive and significant effect on customer satisfaction, with a regression coefficient value of 0.462 and a t-value of 5.159 > 1.666. Service quality also has a positive and significant effect on customer satisfaction, with a regression coefficient value of 0.223 and a t-value of 3.087 > 1.666 and a significance value of 0.000 < 0.05. Together, product quality and service quality have a positive and significant impact on customer satisfaction at Ghathaf Coffee Premium Teupin Punti, North Aceh. The implications of this study highlight the importance for Ghathaf Coffee Premium to continuously improve its product and service quality to maintain and enhance customer satisfaction and strengthen its market position.